Implementation of a Clinical Decision Support Alert for the Management of Clostridium difficile Infection - Sara Revolinski (MDPI AG, 2015)
Clostridium difficile infections are common in hospitalized patients and can result in significant morbidity and mortality. It is imperative to optimize the management of C. difficile infections to help minimize disease complications. Antimicrobial stewardship techniques including guidelines, order sets and other clinical decision support functionalities may be utilized to assist with therapy optimization. We implemented a novel alert within our electronic medical record to direct providers to the C. difficile order set in order to assist with initiating therapy consistent with institutional guideline recommendations. The alert succeeded in significantly increasing order set utilization, but guideline compliance was unchanged.